The targets and linguistic expression of mockery in contemporary jokes on gender - Bandoriūtė, Salomėja (Lietuvių kalba, 2011)
The article concentrates on the targets and linguistic expression on mockery in contemporary jokes on gender. The jokes have been collected from the humour websites www.cha.lt, www.anekdotai.us, www.linksmas.net, www.anekdotai.biz, www.anekdotai.org, www.che.lt. The aim of the research is to find out what types of characters are usually chosen as targets of jokes and what linguistic means are employed to create the comic effect in them. In addition, the article deals with the conception of humour and joke as a genre and provides the key theories of humour research. The study has been carried out applying the method of qualitative content analysis. The results of the study suggest that the choice of the target of mockery in the jokes is often determined by the stereotypes that are common in society and by the tendency to express aggressive emotions in them. Usually the targets of mockery in the jokes are female characters, such as blondes, wives and mothers-in-law. There are approximately three times fewer jokes about men in comparison to women. The most common linguistic means employed to express mockery in the jokes are sarcasm, ambiguity, absurd and irony. It is common to come across cases of a few linguistic means in one joke as well. There has been a connection found between the employed linguistic means and the target of mockery as well as the society’s view to it. The article could be valuable to linguists, folklorists, sociologists and psychologists who investigate the linguistic expression of humour, the effect of emotions on humour and the image of social groups in contemporary jokes.